2022
DOI: 10.1038/s41598-022-22004-7
|View full text |Cite
|
Sign up to set email alerts
|

Seminal extracellular vesicles subsets modulate gene expression in cumulus cells of porcine in vitro matured oocytes

Abstract: Seminal plasma (SP), a fluid composed mainly by secretions from accessory sex glands, contains a heterogenous population of extracellular vesicles (EVs), involved in several reproductive physiological processes. Seminal plasma has been found to modulate ovary function, in terms of hormone secretion and immune regulation. This study evaluated the potential effect of SP-EV-subsets on the modulation of cumulus-oocyte-complex (COCs) physiology during in vitro maturation (IVM). Two SP-EV-subsets, small-EVs (S-EVs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 77 publications
(114 reference statements)
0
5
0
Order By: Relevance
“…In combination with BLM for cancer, abnormal expression of STAR, CYP11A1, and HSD3B1 led to hormone secretion disorder [55]. The secreted progesterone and estradiol of CCs are concerned with the expression of STAR, CYP11A1, and HSD3B1 [57,58]. In this study, the inhibition of CDKN1A significantly increased the mRNA levels of STAR, CYP11A1, and HSD3B1 in bovine CCs and significantly promoted the secretion of E 2 and P 4 .…”
Section: Discussionmentioning
confidence: 51%
“…In combination with BLM for cancer, abnormal expression of STAR, CYP11A1, and HSD3B1 led to hormone secretion disorder [55]. The secreted progesterone and estradiol of CCs are concerned with the expression of STAR, CYP11A1, and HSD3B1 [57,58]. In this study, the inhibition of CDKN1A significantly increased the mRNA levels of STAR, CYP11A1, and HSD3B1 in bovine CCs and significantly promoted the secretion of E 2 and P 4 .…”
Section: Discussionmentioning
confidence: 51%
“…Moreover, Hung et al [ 39 ] showed that both murine and bovine COCs supplemented with EVs derived from bovine FF also significantly increased cumulus expansion during IVM. However, this effect does not always occur, as it has been reported that porcine COCs supplemented with EVs obtained from the physiologically closer porcine FF [ 43 ] or seminal plasma [ 44 ] did not show increased expansion. Similarly, porcine ffEVs did not enhance the expansion of murine COCs [ 43 ].…”
Section: Discussionmentioning
confidence: 98%
“…For experiments with heat stress, treatments were arranged in a 2 × 4 factorial design with primary effects of incubation temperature during maturation (38.5°C vs. 41°C) and with four culture mediums: non-supplemented control (NC), vehicle [DPBS (1X)], EVs derived from granulosa cells subjected to the normal physiological body temperature of the cow (38.5°C) (normal EVs: N-EVs) or EVs derived from granulosa cells subjected to thermal stress (42°C) (stressed EVs: S-EVs). In brief, COCs were incubated with 20% v/v of DPBS (1X), and treatments with GC-EVs were offset with equal concentrations of total protein (0.3 mg/mL) assessed using a NanoDrop 2000 Spectrophotometer (Thermo Scientific; Waltham, MA, United States), selected based on previous literature ( Almiñana et al, 2017 ; Alcântara-Neto et al, 2020a ; Alcântara-Neto et al, 2020b ; Abumaghaid et al, 2022 ; Mateo-Otero et al, 2022 ). For all experimental groups, control COCs matured at a temperature of 38.5°C throughout the maturation period (23 ± 1 h), while thermally stressed COCs were subjected to an initial 8 h priming period at 38.5°C and then transferred to 41°C in an atmosphere of 5% CO 2 in humidified air for the remaining 15 ± 1 h of the 23 ± 1 h maturation period.…”
Section: Methodsmentioning
confidence: 99%